FACTORS CAUSING THE PHENOMENON OF ECONOMY - Rambergenova Rita (Western European Studies, 2025)
The phenomenon of linguistic economy, reflecting the principle of economy in human society, is studied within the context of modern linguistics. This principle emphasizes the reduction of effort in communication, achieved through minimizing speech energy while maximizing information transfer. The phenomenon manifests in various Turkic languages, including Kazakh, Uzbek, and Karakalpak, where phonetic and morphological reductions occur. Various factors, including psychophysiological, social, and time-saving motivations, contribute to linguistic economy. This article reviews related research and explores how this phenomenon emerges within language communities and speech contexts
Keywords: linguistic economy; transfer; phonetic and morphological reductions